Conductive glass powder coating metal bipolar plate for proton exchange membrane fuel cell and preparation method of conductive glass powder coating metal bipolar plate
By coating the surface of the metal substrate with a conductive glass powder coating, the corrosion and contact resistance problems of the metal bipolar plate are solved, high conductivity and durability are achieved, the preparation process is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202510654632.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-09-12
AI Technical Summary
Existing metal bipolar plates in proton exchange membrane fuel cells are prone to corrosion, have high contact resistance, insufficient coating adhesion, complex processes, and high costs, making it difficult to achieve high conductivity and durability.
Conductive glass powder coating is applied to the surface of the metal substrate. A stable network structure is formed by high borosilicate glass powder and corrosion-resistant conductive powder at high temperature. A dense coating is prepared by combining screen printing and high-temperature melting process.
The excellent acid corrosion resistance and high conductivity of the metal bipolar plate are achieved, the contact resistance and corrosion current density are reduced, and good interface bonding performance and performance are ensured. The preparation method is simple and the cost is low.
Smart Images

Figure FT_1 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, and in particular relates to a conductive glass powder coated metal bipolar plate for a proton exchange membrane fuel cell and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cells (PEMFCs) are considered a core technology for hydrogen energy applications due to their high efficiency, low-temperature start-up, and zero-emission characteristics. As a key component of PEMFCs, bipolar plates perform multiple functions: conducting current, distributing reactant gases, discharging reaction products, and supporting the membrane electrode. Developing metal bipolar plate technology that combines high corrosion resistance, low contact resistance, low cost, and scalable manufacturing is a key breakthrough in promoting the commercialization of PEMFCs.
[0003] While traditional graphite bipolar plates offer excellent corrosion resistance and electrical conductivity, they are brittle, expensive to process, and difficult to thin, limiting the power density and commercialization of fuel cells. In recent years, metal bipolar plates (such as stainless steel and titanium alloys) have become a mainstream alternative to graphite bipolar plates due to their high mechanical strength, excellent electrical and thermal conductivity, ease of processing and thinning (thickness can be reduced to less than 0.1 mm), and potential for low-cost, large-scale production. However, metal materials are susceptible to electrochemical corrosion and passivation under the harsh operating conditions of PEMFCs, including strong acidity (pH 2-3), high temperatures (60-80°C), and high potentials (>1V). This leads to metal ion dissolution and contamination of the membrane electrode. Furthermore, the formation of a surface oxide film significantly increases the interfacial contact resistance (ICR), severely degrading cell performance and durability.
[0004] Existing technologies can partially improve corrosion resistance and conductivity through surface modification (such as precious metal coatings, carbon-based coatings, and nitriding). However, these technologies face challenges such as insufficient coating adhesion, complex processes (requiring multiple vacuum coating steps), and high costs (e.g., for gold and platinum coatings). Furthermore, precision forming processes (such as stamping, etching, and 3D printing) for metal bipolar plate channel designs (e.g., serpentine and interdigitated designs) still face challenges such as poor micron-level channel uniformity and low processing efficiency. Further exploration of metal bipolar plates with tight interfacial bonding, excellent corrosion resistance, and high conductivity is of great research and application significance. Summary of the Invention
[0005] The main purpose of the present invention is to address the problems and shortcomings of the existing technology and provide a conductive glass powder-coated metal bipolar plate for proton exchange membrane fuel cells. The conductive glass film is melted onto the surface of a metal substrate to obtain a metal bipolar plate with excellent acid corrosion resistance and high conductivity. The preparation method involved is relatively simple and low-cost, and is suitable for promotion and application.
[0006] To achieve the above solution, the technical solution adopted by the present invention is: A conductive glass powder coated metal bipolar plate for a proton exchange membrane fuel cell comprises a metal substrate and a conductive glass powder coating melted on its surface. The raw materials used in the conductive glass powder coating include glass powder, corrosion-resistant conductive powder and a composite organic carrier, wherein the glass powder is high borosilicate glass powder.
[0007] In the above solution, the raw materials used for the conductive glass powder coating include the following components and their mass percentages: 5-25% high borosilicate glass powder, 50-70% corrosion-resistant conductive powder, and 20-35% composite organic carrier.
[0008] Preferably, the content of high borosilicate glass powder in the raw materials used for the conductive glass powder coating is 5-15%.
[0009] More preferably, the content of high borosilicate glass powder in the raw materials used for the conductive glass powder coating is 5-10%.
[0010] In the above solution, the corrosion-resistant conductive powder can be selected from one or more of silver powder, graphite powder, etc.
[0011] In the above solution, the composite organic carrier comprises ethyl acetate and ethyl cellulose.
[0012] In the above scheme, the composite organic carrier has an ethyl acetate content of 75-85 wt %, and an ethyl cellulose content of 15-25 wt %.
[0013] In the above solution, the B2O3 content in the high borosilicate glass powder is 6-10%.
[0014] Furthermore, the chemical components and their mass percentages in the high borosilicate glass powder include: B2O36-10%, SiO270-78%, Al2O35-13%, ZnO 3-5%, CaO2-4%, ZrO21-3%, BaO 2-4% Furthermore, the high borosilicate glass powder has high mechanical strength, chemical stability, melt fluidity, and low thermal expansion coefficient. After mixing it with corrosion-resistant conductive powder and composite organic carrier, it can promote the formation of a stable network structure between the glass powder and the conductive filler at high temperature. Combined with processes such as screen printing film forming and high-temperature melting, it can promote the acquisition of a corrosion-resistant and conductive coating with a dense surface, good adhesion to the metal substrate and relatively uniform thickness.
[0015] Furthermore, the raw materials used to prepare the glass powder and their mass percentages include: 11-13% boric acid, 3-5% zinc oxide, 68-75% silicon dioxide, 7-9% aluminum hydroxide, 3-4% calcium carbonate, 2-4% zirconium dioxide, and 3-4% barium carbonate.
[0016] Furthermore, the preparation steps of the glass powder include the following: weighing boric acid, calcined zinc oxide, silicon dioxide, aluminum hydroxide, calcium carbonate, zirconium dioxide and barium carbonate according to a proportion and placing them into a crucible, melting them, and quenching them with water to prepare glass slag; mixing the obtained glass slag with a grinding aid (such as anhydrous ethanol), finely grinding the mixture, vacuum drying it, and sieving it multiple times with a filter (200 mesh) to form a powder.
[0017] In the above solution, the metal substrate can be made of stainless steel plate 304, 316 or 316L.
[0018] The present invention also provides a method for preparing a conductive glass powder coated metal bipolar plate for a proton exchange membrane fuel cell, comprising the following steps: 1) Mix glass powder, silver powder and composite organic carrier into slurry according to the proportion, grind until there are no particles, remove bubbles, and print to obtain a conductive glass powder film; 2) Polish and wash the metal substrate; soak the conductive glass powder film in water, take it out and tightly fit it on the washed metal substrate, perform hot pressing to remove air and moisture, and vacuum dry it; then let it stand at room temperature; 3) The obtained sample is subjected to high-temperature heat treatment to melt the conductive glass powder film, and then naturally cooled to room temperature to produce a conductive glass powder-coated metal bipolar plate.
[0019] In the above scheme, the printing step in step 1) uses a 40-60 mesh screen; the printing speed is 5-15 cm / s under a pressure of 0.2-0.4 MPa, and the printing thickness is 150-250 μm; the use of other coating methods such as brushing is not conducive to ensuring the performance of the final metal bipolar plate.
[0020] In the above scheme, in step 2), the washing step includes: soaking in acetone and water for ultrasonic treatment.
[0021] In the above scheme, in step 2), the conductive glass powder film is immersed in water for 1-2 minutes.
[0022] In the above scheme, the temperature used in the hot pressing step is 90-100°C, the pressure is 4-7 MPa, and the time is 10-20 minutes.
[0023] In the above scheme, the temperature used in the vacuum drying step is 110-120°C.
[0024] In the above scheme, the room temperature standing treatment time is 16-24 hours.
[0025] In the above scheme, the target temperature adopted by the high-temperature heat treatment is 560-590°C, and the holding time is 20-40 minutes.
[0026] In the above scheme, the high temperature heat treatment step is performed from room temperature to the target temperature, and the heating rate used is 1-3°C / min.
[0027] The contact resistance of the conductive glass powder coated metal bipolar plate prepared by the above scheme is as low as 1.79mΩ·cm under a pressure of 1.5MPa. 2 , the bulk conductivity reaches 2400S / cm, with excellent conductive properties; under heating and acidic conditions, the corrosion current density of the dynamic potential test can be as low as 0.20μA / cm 2 .
[0028] Compared with the prior art, the present invention has the following beneficial effects: 1) This invention proposes, for the first time, the use of a melting process to deposit a conductive glass powder coating on a metal substrate, producing a metal bipolar plate with excellent acid corrosion resistance and high conductivity. The introduced borosilicate glass powder promotes the formation of a stable network structure with conductive fillers such as silver powder at high temperatures, ensuring good chemical stability and corrosion resistance. 2) The present invention can form a dense conductive glass powder coating on the surface of the metal substrate, thereby protecting the surface of the metal bipolar plate from corrosion while maintaining high conductivity and good interface bonding performance, thereby ensuring the performance of the resulting metal bipolar plate.
[0029] 3) The preparation method of the present invention is relatively simple and low-cost, which can effectively overcome the problems of complex preparation process of existing metal bipolar plate coatings and provide a new idea for the preparation of high-performance metal bipolar plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Surface morphologies of the conductive glass powder-coated metal bipolar plates obtained in (a) Example 1, (b) Example 2, (c) Example 3, and (d) Comparative Example 2. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely for the purpose of explaining the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.
[0032] Example 1 A conductive glass powder coated metal bipolar plate for a proton exchange membrane fuel cell, the preparation method of which comprises the following steps: 1) Weigh the raw materials of boric acid, calcined zinc oxide, silicon dioxide, aluminum hydroxide, calcium carbonate, zirconium dioxide, and barium carbonate in a mass ratio of 11:3:71:7:3:2:3 and place them in a crucible. Place the crucible in a frit furnace, heat it to a maximum temperature of 1300°C, liquefy it, and hold it for 60 minutes to obtain a glass liquid. The obtained glass liquid is then poured into water and quenched into glass slag, which is then weighed. 2) The obtained glass slag and anhydrous ethanol were poured into a grinder in a volume ratio of 2:1, and ground multiple times until the particle fineness was less than 10 μm. The mixture was dried in a vacuum drying oven at 120°C for 5 hours to evaporate the ethanol, and the mixture was sieved multiple times through a 200-mesh filter to obtain glass powder. The chemical components and their weight percentages of the obtained high borosilicate glass powder included: B2O38%, SiO274%, Al2O37%, ZnO3%, CaO3%, ZrO2%, and BaO3%. 3) Accurately weigh ethyl acetate solvent and ethyl cellulose thickener in a mass ratio of 8:2 and place them in a beaker. Stir magnetically at 80°C and 300 rpm until the ethyl cellulose is completely dissolved. Keep warm for 1 hour, then remove and cool to obtain an organic vehicle. The obtained glass powder, silver powder, and organic vehicle are poured into a container in a mass ratio of 5:70:25, stirred to form a slurry, and then finely ground using a three-roll mill until there are no particles. The ground slurry is placed in a degassing machine to remove air to obtain a conductive glass powder slurry; The conductive glass powder slurry was printed using a 50-mesh screen at a printing speed of 10 cm / s under a pressure of 0.2 MPa and an average printing thickness of 200 μm. The film was air-dried and the dried conductive glass powder film was sealed and stored. 316L stainless steel with a size of 20 mm × 20 mm × 1 mm was ground with 600-mesh, 1000-mesh, and 2000-mesh sandpaper, and then polished with 1 μm diamond abrasive paste. After ultrasonic treatment in acetone for 15 min, ultrasonic treatment in deionized water for 15 min was performed to obtain the pretreated stainless steel plate. The prepared conductive glass powder film was soaked in 30℃ deionized water for 1 minute, then taken out and tightly attached to the pretreated stainless steel plate. A hot press was used at 100℃ and 5MPa pressure for 10 minutes to ensure close contact between the film and the stainless steel, and to expel air and moisture. Finally, it was dried in a vacuum drying oven at 90℃ for 4 hours. After standing at room temperature for 24 hours, the obtained sample was placed in a muffle furnace, heated to 580°C over 300 minutes, kept warm for 20 minutes, and naturally cooled to room temperature to obtain a conductive glass powder metal bipolar plate.
[0033] Example 2 A conductive glass powder-coated metal bipolar plate for a proton exchange membrane fuel cell is prepared by a method substantially the same as that of Example 1, except that the mass ratio of the glass powder, silver powder, and organic carrier is adjusted to 15:60:25.
[0034] Example 3 A conductive glass powder-coated metal bipolar plate for a proton exchange membrane fuel cell is prepared by a method substantially the same as that of Example 1, except that the mass ratio of the glass powder, silver powder, and organic carrier is adjusted to 20:55:25.
[0035] Comparative Example 1 A metal bipolar plate for a proton exchange membrane fuel cell is prepared by a method substantially the same as that of Example 1, except that only silver powder and an organic carrier are added to prepare a silver film which is melt-deposited on a 316L stainless steel substrate.
[0036] Comparative Example 2 A conductive glass powder-coated metal bipolar plate for a proton exchange membrane fuel cell is prepared by a method substantially similar to that of Example 1, except that commercially available glass powder is used as the glass powder, and its chemical composition and percentage by mass are as follows: silicon dioxide (SiO2) 73%, sodium oxide (Na2O) 14%, calcium oxide (CaO) 5%, and aluminum oxide (Al2O3) 8%; and the mass ratio of the glass powder, silver powder, and organic carrier is adjusted to 15:60:25.
[0037] Figure 1 The surface morphology of the conductive glass powder-coated metal bipolar plates obtained in Examples 1, 2, and 3 and Comparative Example 2 shows that the coating samples obtained in Examples 1-3 have no obvious defects such as holes or cracks on their surfaces, demonstrating good density. The morphology at high magnification reveals an agglomerated unit cell structure with clear boundaries and a relatively uniform distribution of silver particles on the surface. In contrast, the coating sample obtained in Comparative Example 2 exhibits poor surface density, with localized micropores and a lack of surface grain deposition, which compromises the coating's corrosion resistance and electrical conductivity.
[0038] The test showed that the conductive glass powder coatings obtained in Examples 1 to 3 were tightly bonded to the metal substrate and were not prone to cracking, thereby exhibiting good interface bonding performance.
[0039] The basic physical property test results of the conductive glass powder coated metal bipolar plates obtained in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1, respectively.
[0040] Table 1 Basic physical properties test results of conductive glass powder metal bipolar plates
[0041] The above results show that the metal bipolar plates obtained in Examples 1 to 3 all exhibit good electrical conductivity and have low corrosion current density and contact resistance, meeting the requirements of conductivity of more than 100 S / cm and corrosion current density of less than 1 μA / cm. 2 , contact resistance is less than 10 mΩ·cm 2 standard requirements; at the same time, it has certain waterproof performance and can show good durability.
[0042] It will be easily understood by those skilled in the art that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A conductive glass powder coated metal bipolar plate for a proton exchange membrane fuel cell, characterized in that: It includes a metal substrate and a conductive glass powder coating melted on the surface of the metal substrate. The conductive glass powder coating is made of raw materials including glass powder, corrosion-resistant conductive powder and composite organic carrier, wherein the glass powder is high borosilicate glass powder.
2. The conductive glass powder coated metal bipolar plate according to claim 1, characterized in that: The conductive glass powder coating adopts raw materials, and the components and their mass percentages include: high borosilicate glass powder 5-25%, corrosion-resistant conductive powder 50-70%, and composite organic carrier 20-35%.
3. The conductive glass powder coated metal bipolar plate according to claim 1, characterized in that: The corrosion-resistant conductive powder is one or more of silver powder and graphite powder; and the composite organic carrier comprises ethyl acetate and ethyl cellulose.
4. The conductive glass powder coated metal bipolar plate according to claim 1, characterized in that: The content of B2O3 in the high borosilicate glass powder is 6-10%.
5. The conductive glass powder coated metal bipolar plate according to claim 1, characterized in that: The chemical components and their mass percentages in the high borosilicate glass powder include: B2O3 6-10%, SiO2 70-78%, Al2O3 5-13%, ZnO 3-5%, CaO 2-4%, ZrO 1-3%, and BaO 2-4%.
6. The method for preparing a conductive glass powder coated metal bipolar plate for a proton exchange membrane fuel cell according to any one of claims 1 to 5, characterized in that: The steps include: 1) Mix glass powder, silver powder and composite organic carrier into slurry according to the proportion, grind until there are no particles, remove bubbles, and print to obtain a conductive glass powder film; 2) Polish and wash the metal substrate; soak the conductive glass powder film in water, take it out and tightly fit it on the washed metal substrate, perform hot pressing to remove air and moisture, and vacuum dry it; then let it stand at room temperature; 3) The obtained sample is subjected to high-temperature heat treatment and naturally cooled to room temperature to produce a conductive glass powder-coated metal bipolar plate.
7. The preparation method according to claim 6, characterized in that The printing step uses a 40-60 mesh screen; the pressure used is 0.2-0.4Mpa, the printing speed is 5-15cm / s, and the printing thickness is 150-250μm.
8. The preparation method according to claim 6, characterized in that The temperature used in the hot pressing step is 90-100° C., the pressure is 4-7 MPa, and the time is 10-20 min.
9. The preparation method according to claim 6, characterized in that The room temperature standing treatment time is 16-24 hours.
10. The preparation method according to claim 6, characterized in that The target temperature of the high temperature heat treatment is 560-590° C., and the holding time is 20-40 minutes.